Features of the formation of the investment management mechanism in Ukraine - Vitalii Blahoi; Alevtina Pakulina (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет)
The article conducts a systematic study of the main areas of investment policy based on the long-term strategy of structural restructuring of the economy of Ukraine. The current state of investment activity, the directions of formation and consumption of investment resources in the country are analyzed. Factors that hinder its development. Priority areas for attracting and supporting strategic investors are proposed. The role of the influence of state authorities on the activation of actions to increase the volume and optimize the structure of foreign investment is determined. Ways to improve the investment climate in the construction industry are proposed. Problems of the development of investment activity in Ukraine are considered. Elements of the mechanism for managing investment activity are proposed, taking into account international experience and the specifics of the behavior of the domestic consumer. The investment potential of the Ukrainian economy exceeds the actual volume of investments in the country. Therefore, it is necessary to effectively realize the large investment potential of the Ukrainian economy. To do this, it is necessary to involve all available legal, organizational and economic prerequisites, as well as forms and mechanisms for creating a positive investment image of Ukraine. The formation of an institutional environment favorable to investors is becoming particularly relevant. Within the framework of global economic integration and digital transformation, effective investment management should be based on the principles of sustainable development, long-term strategic planning, and intersectoral coordination. Such an approach will not only increase investment volumes, but also contribute to strengthening Ukraine's position in the international investment market.